Fremde Galaxien und abstrakte Welten Open Access in Astronomie und Mathematik. Soziologische Perspektiven - Taubert, Niels (Science Studies, 2019)
How does open access change science as social practice? By answering that question, this innovative book provides sociology of science with a new subject: information infrastructure research.